Sujet clitique et dynamique de l’écrit : un éclairage par les jets textuels - Quentin Feltgen; Florence Lefeuvre; Dominique Legallois (Discours, 2023)
The dynamics of writing can be studied by resorting to keystroke logging software that records the timestamp of each event in the writing process and keeps track of the revised sequences. These data are usually framed into a sequence of bursts, defined through pauses exceeding a given threshold that segment the flow of events. These bursts are, however, extremely heterogeneous. To shed light on their linguistic contents and motivations, we focus on subject clitics. We show, using a Monte-Carlo-type statistical method, that these clitics are found to a marked degree in the front position of the production bursts. On annotating these clitics in front position, we observed that they often follow a revision event, which hints at the clitics’ role in the resumption of the textual production. Based on a qualitative review of a few selected bursts, we also highlight that the writing hinges upon the grammatical pairing between subject clitic and verb to elaborate discourse strategies that follow the usual theme/rheme order in French sentences. These findings concur to show that the textual bursts are far from random, and that they reflect the function of the linguistic units that they construe into an utterance within the writing production flow.